World Electric Vehicle Journal—Aims and Scope Update - Joeri Van Mierlo (World Electric Vehicle Journal, 2024)
The World Electric Vehicle Journal was started in 2007 with the aim of providing a platform for scientific communications within the field of electric vehicles [...]